2016
DOI: 10.1080/01635581.2016.1187283
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Dietary Folate Intake and Promoter CpG Island Methylation in Clear-Cell Renal Cell Cancer

Abstract: We investigated whether alcohol and dietary folate intakes were associated with promoter methylation in clear-cell renal cell carcinoma (ccRCC). The Netherlands Cohort Study with a casecohort design included 120,852 subjects aged 55-69 yr in 1986. Diet was measured with a foodfrequency questionnaire. After 20.3 yr of follow-up, paraffin-embedded tumor blocks were collected. Methylation-specific polymerase chain reaction (MSP) was used to analyze promoter methylation of 11 genes. ccRCC cases were classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The NEURL on the other hand acts as a tumor suppressor [45] and is involved in the Notch signaling pathway [18,46] which is critical for determination of cell fates within a wide variety of tissues by regulation of growth, differentiation, and apoptosis. Furthermore, several studies revealed that the Notch signaling pathway has an important role in the development of the mammalian kidney whereby several key members of the Notch cascade are expressed during nephrogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…The NEURL on the other hand acts as a tumor suppressor [45] and is involved in the Notch signaling pathway [18,46] which is critical for determination of cell fates within a wide variety of tissues by regulation of growth, differentiation, and apoptosis. Furthermore, several studies revealed that the Notch signaling pathway has an important role in the development of the mammalian kidney whereby several key members of the Notch cascade are expressed during nephrogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…MSP primer design was based on the MBD-affinity massive parallel sequencing data. Detailed information on primer sequences and MSP conditions are available elsewhere 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The 13 papers were published between 1997 and 2018 and they included a total of 13 different study populations (Table 1) [17][18][19][20][21][22][23][24][25][26][27][28][29]. Five of these studies were conducted in Europe, six were in North America, one in Australia, and one in South America.…”
Section: Study Characteristicsmentioning
confidence: 99%